INTEGRASI SOSIAL DALAM PENGURANGAN RISIKO BENCANA: STUDI TENTANG MASYARAKAT MULTIKULTURAL DI DESA PEMENANG BARAT DAN DESA PEMENANG TIMUR KABUPATEN LOMBOK UTARA - Saputra, Hendra Puji; Nursalim, Isnan; Rizkiandi, Rizwan (UNIVERSITAS SEBELAS MARET (UNS), 2023)
The communities in two villages, namely West Pemenang Village and East Pemenang Village, Pemenang District, North Lombok Regency, are unique because they have diversity which becomes their social strength in facing disasters. This form of diversity is represented through 3 religious communities, namely Islam, Hinduism and Buddhism, which live side by side in harmony and tolerance. This research aims to analyze the process of social integration of multicultural communities in Disaster Risk Reduction (DRR) in two villages in Pemenang District using Anthony Giddens structuration theory. This research uses a qualitative method with a multiple case study approach because more than one focus of attention is studied, namely aspects of social integration of multicultural society and disaster aspects. The data collection process was carried out through: observation, in-depth interviews, and documentation. The results of this research show that the process of social integration of multicultural communities in DRR in two villages in Pemenang District is influenced by 3 (three) factors, namely: First, the existence of shared history and collective experiences in the past which are represented philosophically through the concept of